THE USE OF ENGLISH ON ONLINE MEDIA (WHATSAPP BROADCAST) IN FRONT OFFICE DEPARTMENT AT GALERI CIUMBULEUIT HOTEL - Murtala, Alifah A.; Thamrin, Husni; Alwasilah, Senny S.; Maulana, Angga (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
Hotel is one of the places that people choose to spend their time while on vacation or in the context of business. Each hotel certainly has its own way of attracting people to come to their hotel to stay and come back later. Galeri Ciumbuleuit Hotel is one of the hotels that has a unique way of conveying information, especially regarding hotel promos to guests. They use online media (Whatsapp Broadcast) to provide information about hotel promos. Of course they have their own way of sending broadcast messages. They definitely choose a certain style of language to attract customers. As will be discussed in this study, "The Use of English on Online Media (Whatsapp Broadcast) in Front Office Department at Galeri Ciumbuleuit Hotel". This study uses a qualitative approach as the research method which will be explained descriptively. After doing some research and discussion, the results of this study indicate that Hotel Galeri Ciumbuleuit uses two language styles, namely formal and casual style in conveying hotel promos. The final result of this study also shows that the style of language they use tends to be casual style, the choice of words is simple but sufficient to convey the essence of the promos they provide. This explains that they want to make guests feel comfortable when reading the broadcast messages from the hotel. Thus the choice of language style they use in hotel promos is very simple but quite interesting